1996
DOI: 10.1021/om950855y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of 1,4-Bis(pentamethyldisilanyl)butadiyne:  Formation of Silacyclopropene Intermediates

Abstract: Irradiation of 1,4-bis(pentamethyldisilanyl)butadiyne (BPDB) in methanol yields two 1:1 photoaddition products (1 and 2) and one 1:2 photoadduct (3). Adduct 1 is the primary photoproduct while 2 and 3 are the secondary products, 3 being formed via two silacyclopropene intermediates. Irradiation of BPDB with acetaldehyde and acetone in deaerated methylene chloride yields only 1:1 photoadducts (4−6), probably due to the steric effects of the initially formed 1-oxa-2-silacyclopent-3-ene ring preventing the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The first issue that needed to be addressed was the stereochemistry of silirane ring- opening reactions. The stereochemical course of silirane protonolysis 7,25 has not been determined, although the methanolysis of silirenes proceeds with retention of alkene configuration. , Jones demonstrated that the addition of MeOD to adducts of trans -2-butene or cyclohexene and photochemically generated dimethylsilylene gave stereospecific incorporation of a deuterium atom; however, no direct evidence was given for the presence of silirane intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…The first issue that needed to be addressed was the stereochemistry of silirane ring- opening reactions. The stereochemical course of silirane protonolysis 7,25 has not been determined, although the methanolysis of silirenes proceeds with retention of alkene configuration. , Jones demonstrated that the addition of MeOD to adducts of trans -2-butene or cyclohexene and photochemically generated dimethylsilylene gave stereospecific incorporation of a deuterium atom; however, no direct evidence was given for the presence of silirane intermediates.…”
Section: Resultsmentioning
confidence: 99%